Editorial - Heitmeyer, Wilhelm; Massey, Douglas S.; Messner, Steven F.; Sidanius, James; Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2008)
This issue of the International Journal of Conflict and Violence focuses on the topic of anomie/anomia. We would like to thank the guest editors, Steven F. Messner (University of Albany, New York) and Helmut Thome (Martin Luther University, Halle-Wittenberg) for the very fruitful and productive collaboration, and the impressive collection of papers they have put together.